2012
DOI: 10.1177/014556131209100311
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Tumor Size, Degree of Differentiation, and Depth of Invasion on the risk of Neck Node Metastasis in Squamous Cell carcinoma of the Oral Cavity

Abstract: Cervical lymph node metastasis is the most important prognostic factor in patients with head and neck carcinoma. We retrospectively analyzed the effects of three different variables-tumor size, degree of differentiation, and depth of invasion-on the risk of neck node metastasis in 50 adults who had been treated with surgery for primary squamous cell carcinoma of the oral cavity. Primary tumor depth and other pathologic features were determined by reviewing the pathology specimens. Preoperatively, 36 of the 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 33 publications
4
25
0
Order By: Relevance
“…Of note, although important in the TNM system, tumor size was not significantly associated with serum adiponectin level. It is likely that the rate of lymph node metastasis was not associated with increased tumor size, but rather more closely associated with the degree of differentiation in oral cancer, as described previously . Compared with paracancer, TSCC tissues showed higher adiponectin levels at an early stage, when tumors were <4 cm and without lymph node metastasis.…”
Section: Discussionsupporting
confidence: 51%
“…Of note, although important in the TNM system, tumor size was not significantly associated with serum adiponectin level. It is likely that the rate of lymph node metastasis was not associated with increased tumor size, but rather more closely associated with the degree of differentiation in oral cancer, as described previously . Compared with paracancer, TSCC tissues showed higher adiponectin levels at an early stage, when tumors were <4 cm and without lymph node metastasis.…”
Section: Discussionsupporting
confidence: 51%
“…13,30,31 Nodal metastasis is necessary for clinical TNM staging, and it is notable that worse survival is seen in those with positive nodes at diagnosis. 24,25 Anatomical site as well as regional and distant metastasis have been identified as independent prognostic factors for females.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor depth has been shown to be a consistently reliable indicator of occult neck metastases. [42][43][44] Fakih et al, 39 in their RCT examining long-term survival benefits to elective versus therapeutic neck dissection, discovered that patients with tumors with a depth of invasion (DOI) >4 mm were much more likely to have occult regional metastases. Vijayakumar et al 45 looked at 217 carcinomas of the tongue and similarly found that a DOI >4 mm was associated with occult metastases with a rate of 62%.…”
Section: What Does the Literature Say About The Relationship Betweementioning
confidence: 99%
“…Tumor depth has been shown to be a consistently reliable indicator of occult neck metastases . Fakih et al, in their RCT examining long‐term survival benefits to elective versus therapeutic neck dissection, discovered that patients with tumors with a depth of invasion (DOI) >4 mm were much more likely to have occult regional metastases.…”
Section: Introductionmentioning
confidence: 99%